1995
DOI: 10.1148/radiology.196.2.7617861
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic duct: MR cholangiopancreatography with a three-dimensional fast spin-echo technique.

Abstract: MR cholangiopancreatography can accurately demonstrate the normal pancreatic duct as well as various pancreatic duct abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(73 citation statements)
references
References 0 publications
2
68
0
3
Order By: Relevance
“…Specific clinical needs can be answered by gadoliniumchelates enhanced MR imaging, with MRCP during secretin administration, to assess the pancreatic exocrine reserve [132,138,[151][152][153].…”
Section: I4mentioning
confidence: 99%
“…Specific clinical needs can be answered by gadoliniumchelates enhanced MR imaging, with MRCP during secretin administration, to assess the pancreatic exocrine reserve [132,138,[151][152][153].…”
Section: I4mentioning
confidence: 99%
“…Soto et al [18] found the sensitivity of MRCP for dilatation as 87%-100%, for narrowing 75%, and for ductal calculi 100%. The authors conclude that MRCP can accurately demonstrate pancreatic duct abnormalities in chronic pancreatitis.…”
Section: Mrcp In Chronic Pancreatitismentioning
confidence: 99%
“…It has now assumed the position of modality of choice in the evaluation of biliary tree and pancreatic duct. 5,6,7,8,9 AIM OF THE STUDY Aim of the study is to compare Magnetic Resonance Cholangiopancreatography (MRCP) and Endoscopic Retrograde Cholangiopancreatography (ERCP) in the evaluation of biliary obstruction. Reference standards for comparison were surgery or biopsy taken laparoscopically.…”
Section: How To Cite This Articlementioning
confidence: 99%